2002
DOI: 10.1046/j.1524-4741.2002.08406.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Self-Examination: Knowledge, Attitudes, and Practices Among Female Health Care Workers in Tehran, Iran

Abstract: A cross-sectional study was conducted to examine the knowledge of breast cancer, attitudes toward breast self-examination (BSE), and practice of BSE among a sample of female health care workers in Tehran, Iran. Using a purposed questionnaire, a total of 410 women from seven health centers completed the questionnaire. The mean age of the respondents was 32.9 years (SD = 9.5), most (58%) were married, and family history of breast cancer was reported by 11%. Seventy-five percent of the women knew about breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
125
6
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(164 citation statements)
references
References 15 publications
27
125
6
2
Order By: Relevance
“…In another Turkish (185) No (256) Yes (40) No (401 (Karahan et al, 2006). In contrast of our study result, Haji-Mahmoodi et al, have found that that only 6% of female health care workers in Tehran performed BSE monthly (Haji-Mahmoodi et al, 2002). In a Norwegian study Rosvold et al, have reported that only 25.6% female workers performed monthly BSE (Rosvold et al, 2001).…”
Section: Discussioncontrasting
confidence: 98%
“…In another Turkish (185) No (256) Yes (40) No (401 (Karahan et al, 2006). In contrast of our study result, Haji-Mahmoodi et al, have found that that only 6% of female health care workers in Tehran performed BSE monthly (Haji-Mahmoodi et al, 2002). In a Norwegian study Rosvold et al, have reported that only 25.6% female workers performed monthly BSE (Rosvold et al, 2001).…”
Section: Discussioncontrasting
confidence: 98%
“…breast cancer, its screening and risk factors increasing as the monthly household income increased. Similar cases have been reported for most Asian and African countries (Rashidi and Rajaram, 2000;Haji-Mahmoodi et al, 2002;Okobia et al, 2006;Heidari et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…The lack of knowledge, however, did not always present as the reason for the lack of BSE practice. Studies among the nurses of Lagos, Nigeria; school teachers of Buraidah, Saudia and lady health workers of Tehran, Iran suggested that regardless of women being educated in the field of science, they had little knowledge of the breast cancer screening methods (Odusanya, 2001;Dandash and Al-Mohaimeed, 2007;Haji-Mahmoodi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that doctors often do not offer BCS services to women. Other health care providers (HCP) might not have adequate knowledge of BCS and risk factors related to breast cancer in the Middle East, thus limiting their ability to encourage patients to engage in BCS activities (Bener et al, 2001;Haji-Mahmoodi, 2002;Madanat and Merrill, 2002;Dow Meneses and Yarbro, 2007;Alkhasawneh et al, 2009;Jaradeen, 2010;El Hajj and Hamid, 2011). Previous studies in the region indicate low participation rates in breast cancer screening activities among women (Bener et al, 2001;Bener et al, 2002;Azaiza and Cohen, 2008;Bener et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and varied sources of information about breast health and BCS from health care providers (especially physicians), mass media, and social networks can positively influence women's knowledge and practice of BCS (Al-Qattan, et al, 2007;Dandash and Al-Mohaimeed, 2007;Montazeri, et al, 2008;Hoffman et al, 2010). Facilitators of BCS behavior include having support from male relatives, receiving information about breast cancer or BCS from health care professionals (HCP) other than doctors, and having a doctor's recommendation (Haji-Mahmoodi, 2002;Madanat and Merrill, 2002;Cohen and Azaiza, 2005;Azaiza and Cohen, 2006;Shirazi et al, 2006;Dandash and Al-Mohaimeed, 2007;Dow Meneses and Yarbro, 2007;El Saghir et al, 2007;Alkhasawneh et al, 2009;Gürsoy et al, 2009;Jaradeen, 2010;El Hajj and Hamid, 2011).…”
Section: Introductionmentioning
confidence: 99%